HUBUNGAN DEBIT AIR DAN TINGGI MUKA AIR DI SUNGAI LAMBAGU KECAMATAN TAWAELI KOTA PALU - Abdul Kamal Neno; Herman Harijanto; Abdul Wahid (Jurnal Warta Rimba, 2017)
The measurement of waterflow debit is very needed to know the potency of water resource at a  river flow area. Debit is the  water volumethat flows in one time. The consentration time is a needed time for rainfall running off for the farest spot to the control observed spot. The measurement of waterflow speed can be used as a tool to monitor and evaluate water balance at one area by approaching the potency of existing surface water resource. The aimed of the research is to find out the correlation of water debit and water surface height at Lambagu River Tawaeli District Palu City. The research was conducted on February to April 2015 at River Lambagu Tawaeli District Palu City. Furthermore, the data gathered involved primary data; data gathered in the location directly, they were the data of the width of river wet profile, the length of river wet profile, the depth of river wet profile, the speed of riverflow, the height of  surface water, abd rainfall while  the secondary data was the data that gathered from library, literature, available reports of office and involved institution, as a supporting data that involved: topography condition, geomorphologi, land covering, rainfall around Lambagu Riverflow Area for last 4 years that gathered from Palu-Poso BPDAS and climate condition at Lambagu River of Tawaeli District Palu City. After research procedures were done, the data gathered analyzed by  using  logaritme method.The result of the research showed that the water debit at Lambagu river Pantoloan subdistrict during the reserach period had the average rate of  0.757 m³/second and the height of water surface at Lambagu river was about0.26 m. The correlation between water debit and water surface height showed a strong (positive) correlation in formula of Q = 0.157h0.654x  with the rate of correlation (R2)=0.905.Keywords :Water Debit, Height of water Surface, Riverflow Area.